2021
DOI: 10.1177/03611981211012423
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Non-Aeronautical Revenues on Airport Landing Charge in Global Airports

Abstract: The airport industry, which is heavily regulated, has shown interest in improving performance by increasing non-aeronautical revenues (NAR) to cope with changes in the aviation environment, including trends toward liberalization and privatization. This study uses panel data from three separate years (2012, 2014, and 2016) to analyze how a high NAR share might affect airport charging policies and explores the impact of NAR on landing charges of global airports grouped by type of aircraft. The data was collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…However, there was less focus on the diversion attribute of airport service quality. While the participants may have considered the diversion attribute as a complex project requiring the redesign of physical aspects of the airport, several studies [26][27][28] pointed out that Non-Aeronautical Revenues (NAR), such as commercial areas, play a vital role, not only concerning passenger satisfaction but also in providing revenue to the airport. Therefore, it is suggested that future studies examine how design thinking could be implemented to enhance the diversion attributes of the airport.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was less focus on the diversion attribute of airport service quality. While the participants may have considered the diversion attribute as a complex project requiring the redesign of physical aspects of the airport, several studies [26][27][28] pointed out that Non-Aeronautical Revenues (NAR), such as commercial areas, play a vital role, not only concerning passenger satisfaction but also in providing revenue to the airport. Therefore, it is suggested that future studies examine how design thinking could be implemented to enhance the diversion attributes of the airport.…”
Section: Discussionmentioning
confidence: 99%